Künstlerhaus Dortmund : 20 Jahre - 20 Ausstellungen : das Jubiläumsjahr 2003. - Schmieder, Peter (Dortmund : Künstlerhaus Dortmund, 2003)
Butt, Katja ; D'Hondt, Lieve ; Dirzys, Redas ; Gerber, Gabriela & Lukas Bardill ; Hayashi, Nobuko ; Herdin, Christine ; Hukuda, Atsuo ; Kreimeyer, Wilhelm ; Kuhl, Annette ; Mayer, Gerhard ; van Otterdijk, Charles ; Panhuysen, Paul ; Posdiena, Dorothea ; Potrony, Albert ; Schlichting, Dirk ; Spanier, Wolfgang ; Stegat, Christiane ; Trantenroth, Tim ; Willeke, Markus ; de Zeeuw, Mirjam
20 tentoonstellingen in 2003 vanaf 2003-01-10
biog., prijzen, ind. tent., gr. tent. p. 2-14 (bijlage)
Duits
boek